1999
DOI: 10.1021/ac980770h
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Amperometric Verification of PCR Amplification of DNA

Abstract: Amplification of an 800-base template was verified in a 10-min test on a 2-microL sample of the PCR product solution. For verification, digoxigeninylated primers and biotinylated d-UTP-16-biotin were added to the amplification solution. The resulting amplified product was digoxigeninlabeled at its 3'-end and was also labeled with multiple biotin functions along its chain. The detecting electrode was coated with an electron-conducting redox hydrogel to which anti-digoxin monoclonal antibody was covalently bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 12 publications
0
50
0
1
Order By: Relevance
“…When the target hybridizes with the probe, the hybrid formation can be electrochemically transduced by a number of indicator-based or indicator-free approaches. The former approach relies on the binding of intercalators [4, 6 ± 9], redox enzymes [10,11], or metal nanoparticles [12 ± 17] onto the hybrid while the latter approach is based on the intrinsic electroactivity of DNA [18,19] or changes in interfacial properties [20 ± 22].…”
Section: Introductionmentioning
confidence: 99%
“…When the target hybridizes with the probe, the hybrid formation can be electrochemically transduced by a number of indicator-based or indicator-free approaches. The former approach relies on the binding of intercalators [4, 6 ± 9], redox enzymes [10,11], or metal nanoparticles [12 ± 17] onto the hybrid while the latter approach is based on the intrinsic electroactivity of DNA [18,19] or changes in interfacial properties [20 ± 22].…”
Section: Introductionmentioning
confidence: 99%
“…The amplicon can be attached directly onto a GEC surface by simple ™dry-adsorption∫ (the simplest immobilization method and the easiest to automate), avoiding the use of procedures based on previous activation of the surface transducer and subsequent immobilization, which are tedious, expensive and time-consuming [37]. The DNA binds strongly to GEC in a way that prevents the strands from self -associating, while at the same time permitting its hybridization to complementary DNA in connection with a short alkaline denaturing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[34] A few groups have used this ECD technique for nucleic acid amplification product detection. [34][35][36][37] In 2003, Lee et al reported the first integrated microchip-based PCR with ECD functionality.…”
Section: Post-pcr Detectionmentioning
confidence: 99%